THE EFFECT OF MICRO-ELEMENTS ON GROWTH, FRUITS AND OIL FENNEL PLANT Foeniculum vulgare L. 1- VEGETATIVE GROWTH - Mothafer A. Al-Mosuly (Mesopotamia Journal of Agriculture)
Fruits planted in the field is sweet bean sheets (1x2 m2) of soil type Silty Loam on 15.10.2006, using four levels of major elements (nitrogen, phosphorus and potassium) are N0P0K0 , N60P30K20 , N90P45K30 and N120P60K40 kg. ha - 1 by using urea, single super phosphate and potassium sulfate as a source of elements, with the elements is small (2.5% Iron , 2.5% zinc ,0.5% manganese and 0.5% copper) are five levels (0, 0.50, 1.5, 2.5, 3.5) gm.liter -1 foliar spray and land, three iterations , harvested plants in 15/5/2007, and the results were : over-treatment N90P45K30 + 2.5 gm . liter -1 of micronutrients, Wet weight of the shoot 33212 kg. foliar spray ha -1 and 28235 kg. ha -1 ground. The dry weight of shoots 3690 kg. foliar spray ha -1 and 2488 kg. ha -1 ground. The number of flowering per plant 30.4 foliar spray and 28.6 ground.